Comparison of GPS derived variables based on home versus away matches in the Asian professional soccer team - Nobari, Hadi (2022)
Professional soccer with high training loads is defined with weekly competition. The purpose of this study was to com pare external training load data of GPS derived variables that preceded a home versus away match. Twenty-two weeks of a national league meet schedule were analyzed, which included 11 home and 11 away matches. Twelve professional soccer players (age, 28.6 6 2.7 years; height, 182.1 6 8.6 cm; BMI, 22.6 6 0.7 kg/m2 ) participated in this study. All matches were monitored using GPSPORTS systems Pty Ltd. The following variables were selected: total duration of the matches and training sessions, high-speed running distance (18–23 km h21 ), sprint distance (. 23 km h21 ), maxi mal speed, body load, metabolic power, accelerations Zone1 (\ 2ms22 ) (AccZ1), accelerations Zone2 (2 –4 m s22 ) (AccZ2), accelerations Zone3 (. 4ms22 ) (AccZ3), decelerations Zone1 (\ 22ms22 ) (DecZ1), decelerations Zone2 (22 to 24ms22 ) (DecZ2) and decelerations Zone3 (. 24ms22 ) (DecZ3). The results indicated that meta bolic power showed higher values at home than away matches [p = 0.047, ES = 0.53, (20.28, 1.34)]. Furthermore, there was a higher value in accumulated external training load that preceded away matches for high-speed running and lower value [p \ 0.001, ES = 20.95 (21.79, 20.10)] for DecZ1 than home matches. In conclusion, external load variables had a higher value in home matches. However, the results showed that high-speed running was higher in away matches, which could be the discretion of the coaches to prepare players for different conditions on the oppo nent’s field.